2017
DOI: 10.1016/j.bbr.2017.04.023
|View full text |Cite
|
Sign up to set email alerts
|

Effects of muscarinic receptor antagonists on cocaine discrimination in wild-type mice and in muscarinic receptor M 1 , M 2 , and M 4 receptor knockout mice

Abstract: Muscarinic M1/M4 stimulation can reduce abuse-related effects of cocaine and may represent avenues for treating cocaine addiction. Muscarinic antagonists can mimic and enhance effects of cocaine, including discriminative stimulus (SD) effects, but the receptor subtypes mediating those effects are not known. A better understanding of the complex cocaine/muscarinic interactions is needed to evaluate and develop potential muscarinic-based medications. Here, knockout mice lacking M1, M2, or M4 receptors (M1-/-, M2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…Co-immunoprecipitation from rat cortical membrane of GABA B2 subunit together with the muscarinic M 2 receptor confirmed in vivo proximity (Boyer et al, 2009) and suggested that the heteromer may play a role in drug addiction by modulating the endogenous acetylcholine tone at presynaptic level. A possible outcome would be a contribution of these heteromers to the discriminative stimulus properties of cocaine (Joseph and Thomsen, 2017).…”
Section: Muscarinic M 2 -Metabotropic Gaba B2 Heteromersmentioning
confidence: 99%
“…Co-immunoprecipitation from rat cortical membrane of GABA B2 subunit together with the muscarinic M 2 receptor confirmed in vivo proximity (Boyer et al, 2009) and suggested that the heteromer may play a role in drug addiction by modulating the endogenous acetylcholine tone at presynaptic level. A possible outcome would be a contribution of these heteromers to the discriminative stimulus properties of cocaine (Joseph and Thomsen, 2017).…”
Section: Muscarinic M 2 -Metabotropic Gaba B2 Heteromersmentioning
confidence: 99%
“…This agent was also 4–10 times more potent than the widely used M1 antagonist pirenzepine (Eltze et al, 1985). Thus, telenzepine is being frequently used to clarify the functional role of M1 receptors in vivo (Tanda et al, 2007; Ztaou et al, 2016; Joseph and Thomsen, 2017). Indeed, an i.p.…”
Section: Discussionmentioning
confidence: 99%
“…We first evaluated the role of striatal M1 and M4 receptors. A systemically active antagonist with moderate subtype selectivity for M1 receptors, telenzepine (Doods et al, 1987; Tanda et al, 2007; Ztaou et al, 2016; Joseph and Thomsen, 2017), or M4 receptors, tropicamide (Lazareno et al, 1990; Ztaou et al, 2016), was injected to adult rats. Their effects on ERK phosphorylation were examined in the two subdivisions of the striatum, the caudate putamen (CPu) and nucleus accumbens (NAc).…”
Section: Introductionmentioning
confidence: 99%
“…At 1 week after surgery, all rats underwent a severe hypoglycemic clamp as described above. [18,19]; n 5 13).…”
Section: Protocol 3: Surgical Vagotomymentioning
confidence: 99%